2012
DOI: 10.1111/j.1365-2621.2011.02907.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterisation of the hydrocolloid from Brea tree (Cercidium praecox)

Abstract: The Brea gum (BG) is a hydrocolloid obtained as phloematic exudate from Cercidium praecox. The exudate was purified by solution and subsequent drying. BG showed high solubility in water 28.3% at 25°C that increased as temperature was raised. Viscosity of BG solutions increased with BG concentration increase and temperature decrease. Addition of acid or alkali produced changes in solution viscosity as the electrostatic charges on the macromolecule were altered. Solution density at 25°C increased linearly with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…WSI results revealed that the percentage of water soluble solids increased with the addition of BG, and this increase was significant (p < 0.05), indicating that the hydrocolloid is not incorporated into the precipitate, because of its high water solubility (28% at 25 °C) (Bertuzzi et al, 2012). The gum was almost completely solubilized in the supernatant, indicating the high affinity of the gum for water, and, probably, there is no synergistic interaction between the wheat starch and BG (Funami et al, 2008).…”
Section: Wai and Wsimentioning
confidence: 99%
See 3 more Smart Citations
“…WSI results revealed that the percentage of water soluble solids increased with the addition of BG, and this increase was significant (p < 0.05), indicating that the hydrocolloid is not incorporated into the precipitate, because of its high water solubility (28% at 25 °C) (Bertuzzi et al, 2012). The gum was almost completely solubilized in the supernatant, indicating the high affinity of the gum for water, and, probably, there is no synergistic interaction between the wheat starch and BG (Funami et al, 2008).…”
Section: Wai and Wsimentioning
confidence: 99%
“…With their extensive root system, brea trees can be found in semi-arid regions of Argentine. Brea trees grow scattered in the wild, and gum from these untended trees is collected manually by native people (Bertuzzi et al, 2012). The exudates gum is obtained from superficial incisions made in the branches and tree trunk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrocolloid gums are structurally complex substances with high molecular weight and with characteristics of elasticity and adhesion. Brea gum (BG) is an exudate from the Brea tree ( Cercidium praecox ) (Ruiz & Pavon Harms) [= Parkinsonia praecox (Ruiz & Pavon) Hawkins] . According to Bertuzzi et al , BG has physicochemical characteristics and functional features similar to those of gum arabic (GA).…”
Section: Introductionmentioning
confidence: 99%